Follow-up research about juvenile degree school students’ entrepreneur intentions and entrepreneur roles. Post-doc –study in the context of international entrepreneurship education - Erkki Nevanpera (Studia z Teorii Wychowania)
Th e purpose of the article is to fi nd possible prospective entrepreneurial roles and intentions of second degree students. In addition, it is being studied whether the future entrepreneurial roles and intentions of high school students are diff erent compared to the data obtained 10 years ago.Th e aim of this quantitative study is to fi nd out the following: 1. What kinds of future entrepreneurial roles and intentions have second degree students now? 2. What is the diff erence between the Finnish schools and the two Polish schools? 3. Are there diff erences between the diff erent genders? 4. What is the eff ect of role models, that is, fatherhood, motherhood and kinship / friendship with entrepreneurship?In addition, it is being studied 5. Whether the future entrepreneurial roles and intentions of high school students are diff erent compared to the data obtained 10 years ago.Demographic factors include gender, school, entrepreneurial and non-entrepreneurial background, as well as entrepreneurship of a close relative / friendship circle. Th e study produces comparative data from two diff erent countries by comparing the entrepreneurial outlook.Th e material was collected in autumn 2014 by a co-meter Nevanperä (2003). Th e meter and its components have been tested several times: Nevanperä & Kansikas (2008) and (2009), Nevanperä (2014) and at the University of Eastern Finland and VaasaIn research sections C and D, a total of 39 claims (future entrepreneurial roles and intentions of students) were factored into fi ve factors to facilitate the processing of results. Th e Likert scale of 1-5 was used in the study. Th e reliables of variables (Cronbach alfas) were high except one (0.63-0.96).Th ere are a total of 324 respondents, of whom 100 are foreign. 38% of Finnish respondents are girls and 58% of foreign respondents are girls. Finnish students in the study are from 40 municipalities and cities in Finland.In the 2006-2007 survey Teuva high school had 21 respondents, Kopernikus high school 112 respondents and Evangelical high school 31 respondents. Polish students live in Cieszyn town, in southern Poland and in the surrounding Silesian provinceTh e study institutes are Suupohja Vocational Institute / Vocational College (92 respondents, 31% girls), Suupohja Vocational Institute / Commercial College (64 respondents, girls 47%), Suupohja Vocational Institute / Agricultural College (29 respondents, girls 18%). Teuva High School (39 respondents, 53% girls; year 2006 21 respondents, 5% girls), Polish Copernicus High School (61 respondents, 62% girls; year 2007 112, 52% girls) and Poland Evangelical High School (39 respondents, 51%; year 2007 31 respondents, 45% girls). Th e research data has been based on statistical means, deviations, meanings (variance analysis / ANOVA), linear regression analysis and t-test in University of Applied Sciences Seinäjoki.Th ere are considerable diff erences between educational institutions in attitudes towards future entrepreneurial roles and intentions. Th e future entrepreneurial roles and intentions of the Polish high school students are signifi cantly more positive than the roles and intentions of the Finnish high school students. Gender and entrepreneurship background explain most young people’s future entrepreneurial roles and intentions. Other background variables also seem to have an eff ect.Th e explanation for the family entrepreneur’s role and intention is the highest when considering the control variables. Th ese explain 19 % of the variation. Relatively, most explains the father’s entrepreneurial background and the second most gender (girl). Girls regard family business and continuing of the family business very signifi cantly less than boys. Father’s entrepreneurial attitude raises the mean very signifi cantly compared to other students. Mother’s entrepreneurial background also has an uplift ing eff ect.Subcontracting and business entrepreneurship are of interest to today’s high school students. However, there are no signifi cant diff erences between the reference years. Th e mean of family entrepreneurship in 2015 is almost signifi cantly higher than in 2006-2007. Also in the case of other analyzes, in which the results of comparisons was the data acquired in 2006-2007 and in 2015, interesting results were obtained, indicating changes that have occurred in the discussed area.